Adolescent Student Burnout Inventory in Mainland China: Measurement Invariance Across Gender and Educational Track. (June 2014) - Li, Bi; Wu, Yan; Wen, Zhonglin; Wang, Mengcheng
This article assessed the measurement invariance of the Adolescent Student Burnout Inventory (ASBI) across gender and educational track, and investigated the main and interaction effects of gender and educational track on the facets of student burnout with a sample consisting of 2, 216 adolescent students from China. Multigroup confirmatory factor analysis was used to test measurement invariance of the ASBI, and the Multiple-Indicator, Multiple-Cause Models (MIMIC) was used to test the main and interaction effects of gender and educational track on the facets of student burnout. Results showed that the three-factor (exhaustion, cynicism, and reduced efficacy) structure of student burnout was invariant across gender and educational track. It was also shown that boys suffered more cynicism than girls; the educational track affected the student burnout; the interaction effect of gender and educational track were found on reduced efficacy in Grade 9 students, and on exhaustion and reduced efficacy in Grade 12 students.